Helicobacter pylori Induces Vascular Endothelial Growth Factor Production in Gastric Epithelial Cells Through Hypoxia‐Inducible Factor‐1α‐Dependent Pathway. Issue 6 (18th September 2014) - Kang, Min‐Jung; Song, Eun‐Jung; Kim, Bo‐Yeon; Kim, Dong‐Jae; Park, Jong‐Hwan
Abstract: Background: Although Helicobacter pylori have been known to induce vascular endothelial growth factor (VEGF) production in gastric epithelial cells, the precise mechanism for cellular signaling is incompletely understood. In this study, we investigated the role of bacterial virulence factor and host cellular signaling in VEGF production of H. pylori ‐infected gastric epithelial cells. Materials and methods: We evaluated production of VEGF, activation of nuclear factor nuclear factor‐kappaB (NF‐κB) and mitogen‐activated protein kinases (MAPKs) and hypoxia‐inducible factor‐1α (HIF‐1α) stabilization in gastric epithelial cells infected with H. pylori WT or isogenic mutants deficient in type IV secretion system (T4SS). Results: H. pylori induced VEGF production in gastric epithelial cells via both T4SS‐dependent and T4SS‐independent pathways, although T4SS‐independent pathway seems to be the dominant signaling. The inhibitor assay implicated that activation of NF‐κB and MAPKs is dispensable for H. pylori ‐induced VEGF production in gastric epithelial cells. H. pylori led to HIF‐1α stabilization in gastric epithelial cells independently of T4SS, NF‐κB, and MAPKs, which was essential for VEGF production in these cells. N‐acetyl‐cysteine (NAC), a reactive oxygen species (ROS) inhibitor, treatment impaired H. pylori ‐induced HIF‐1α stabilization and VEGF production in gastric epithelial cells. Conclusion: We defined the important role of ROS‐HIF‐1α axis in VEGF production of H. pylori ‐infected gastric epithelial cells, and bacterial T4SS has a minor role in H. pylori ‐induced VEGF production of gastric epithelial cells.